2021
DOI: 10.21873/anticanres.14825
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Assessment of TNFAIP3/A20 Expression Correlates With Early Tumorigenesis in Breast Cancer

Abstract: Background/Aim: Limited data exist on the expression pattern of TNFAIP3/A20, as assayed by immunohistochemistry (IHC), in breast cancer tissues. This study aimed to assess A20 expression pattern in breast cancer. Materials and Methods: The expression of A20 was analysed using IHC in 50 breast cancer cases retrieved from the Sharjah Breast Cancer Center at the University Hospital Sharjah, United Arab Emirates. Omics survival data were also used to analyse its association with survival in endocrine-treated subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As the phosphorylation gene of MAPK protein, NRAS has become one of the taxonomic markers of four subtypes of melanoma [44]; moreover, high expression of NRAS is associated with poor prognosis of lung adenocarcinoma [45]. Tumor extracellular vesicles carrying miR-125b-5p enter diffuse large B-cell lymphoma (DLBCL) cells and target TNFAIP3, thereby reducing the sensitivity of DLBCL to rituximab [46], and overexpression of TNFAIP3 is associated with a lower survival rate in breast cancer patients [47]; a study about ferroptosis after cerebral hemorrhage also find TNFAIP3 upregulation [48]. Our model predicted TSCC patient survival in the validation cohorts at 1 year (AUC = 0.889) and 32 months (AUC = 0.9).…”
Section: Discussionmentioning
confidence: 99%
“…As the phosphorylation gene of MAPK protein, NRAS has become one of the taxonomic markers of four subtypes of melanoma [44]; moreover, high expression of NRAS is associated with poor prognosis of lung adenocarcinoma [45]. Tumor extracellular vesicles carrying miR-125b-5p enter diffuse large B-cell lymphoma (DLBCL) cells and target TNFAIP3, thereby reducing the sensitivity of DLBCL to rituximab [46], and overexpression of TNFAIP3 is associated with a lower survival rate in breast cancer patients [47]; a study about ferroptosis after cerebral hemorrhage also find TNFAIP3 upregulation [48]. Our model predicted TSCC patient survival in the validation cohorts at 1 year (AUC = 0.889) and 32 months (AUC = 0.9).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the UAE found that A20 expression evaluated through immunohistochemistry (IHC) was associated with early grade 1 BC (p < 0.001) in all molecular subtypes, suggesting its use as a biomarker for early cancer. A20 overexpression was also associated with a lower OS rate in patients treated with endocrine therapy [60]. Another study found that insulin-like growth factor 1 receptor (IGF1R) membranous and mixed (membranous and cytoplasmic) expression in BC cells was evident in HR + HER2− cases in contrast with HR−HER2+ cases, which showed cytoplasmic or diminished IGF1R expression, suggesting that luminal subtypes may benefit from targeted IGFR therapy [61].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…In recent years, it has been reported that A20 is involved in the pathological progression of breast cancer. Sharif-Askari et al (18) found that A20 could serve as a biomarker for early diagnosis of breast cancer. Song et al (19) confirmed that A20 was involved in inflammation-mediated metastatic disease in triple-negative breast cancer.…”
Section: Introductionmentioning
confidence: 99%